2022
DOI: 10.1155/2022/1206914
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Probiotic Supplementation on Opioid-Related Disorder in Patients under Methadone Maintenance Treatment Programs

Abstract: Introduction. Patients under methadone maintenance treatment programs (MMTPs) are susceptible to numerous complications (e.g., mental and metabolic disorders). This study evaluated the effects of probiotics on clinical symptoms, biomarkers of oxidative stress, inflammation, insulin resistance, and serum lipid content in patients receiving MMTPs. Materials and Methods. A randomized, double-blind, placebo-controlled trial was conducted among 70 patients receiving MMTPs to receive either 1.8 × 109 CFU/day probiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Furthermore, a study reported that administering probiotic supplementation improved the symptoms of depression in patients undergoing MMT programmes while having little to no effect in anxiety and sleep quality. 37 A systematic analysis that relied on existing clinical trials revealed that probiotic supplements had short-term impacts on gut microbiota among MDD patients, and induced modest effects on depressive symptoms. 38 Ranjbar et al 39 showed that zinc supplementation along with antidepressant drugs, effectively improved depressive disorders in major depressive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study reported that administering probiotic supplementation improved the symptoms of depression in patients undergoing MMT programmes while having little to no effect in anxiety and sleep quality. 37 A systematic analysis that relied on existing clinical trials revealed that probiotic supplements had short-term impacts on gut microbiota among MDD patients, and induced modest effects on depressive symptoms. 38 Ranjbar et al 39 showed that zinc supplementation along with antidepressant drugs, effectively improved depressive disorders in major depressive patients.…”
Section: Discussionmentioning
confidence: 99%